Weak Measurements of the Dipolar Emitter Polarization State - Nechayev, Sergey; Neugebauer, Martin; Vomdran, Martin; Leuchs, Gerd; Banzer, Peter (2018 Photonics North, PN 2018, 2018)
We investigate polarization singularities (C points) in the far-field of an elliptically polarized dipole. For an almost linear dipole moment, four singularities occur along directions almost aligned with the dipole moment axis - in the null intensity region. Under certain assumptions measuring two of the C points is enough to fully characterize the dipole's polarization state. We experimentally resolve these C points via weak measurement far-field polarization projection. We propose practical applications for the fundamental study of dipolar emitters in general and position sensing in particular.
CRIS-Team Scopus Importer:2023-04-20
Keywords: dipolar emitters; Far-field; points; polarization singularities; Weak measurements